Applying the Teaching Games for Understanding Model to 4 vs 4 Soccer Games: A Strategy to Improve Shooting Skills - Faridatul ‘Ala, Faridatul ‘Ala; Rahmalia, Apriyanti; Arsil, Arsil; Alnedral, Alnedral; Irawan, Roma (Indonesian Journal of Sport Management, 2025)
Shooting proficiency is a fundamental skill in soccer that significantly influences a team's success. Traditional training methods often focus on technical aspects, potentially neglecting the tactical understanding and decision-making required in dynamic match situations. This study aims to enhance soccer players' shooting skills through the modification of 4 vs 4 games utilizing the Teaching Games for Understanding (TGfU) training model. This study employed an experimental design with pre-test and post-test measurements involving soccer players participating in a specialized training program. Data were collected through observation and assessment of shooting skills using the Loughborough Soccer Shooting Test (LSST) instrument. The results of the independent t-test indicated a significant difference between the pretest and posttest scores of the experimental group, with the t-value (9.26) being greater than the t-table value (2.04). These findings demonstrate that the implementation of the Teaching Games for Understanding (TGfU) model in 4 vs 4 football games significantly improves students' shooting skills. These findings underscore the importance of incorporating tactical-focused training methods to develop comprehensive soccer skills. Implementing such approaches in coaching practices can lead to more effective skill acquisition and performance in competitive settings. Future research should explore the long-term effects of TGfU-based training on various skill sets across different age groups and competitive levels.